Effects of Competitive Wrestling Bouts on Physiological Measures: A Systematic Review and Meta-Analysis [Auswirkungen Von Kompetitiven Ringkämpfen Auf Physiologische Maßnahmen: Eine Systematische Überprüfung Und Metaanalyse] - Aedo-Munoz, E (Elsevier GmbH, 2020)
Present article provides a critical overview of the current literature on the effects of competitive wrestling on neurophysiological parameters. Electronic databases were used to locate relevant studies up to July 2018. Peer reviewed studies using experimental research designs, measurements during wrestling tournaments, neural and physiological parameters (i.e. heart rate -HR, lactate concentration –[LA], bearhug and handgrip strength tests) were addressed. The main results demonstrated a large effect pre vs. post bouts measures of all physiological parameters, highlighting HR (range: 69.8 ± 1.9 bpm to 112 ± 15 bpm vs. 112 ± 15 bpm to 192 ± 9 bpm), [LA] (1.1 ± 0.4 mmol/L to 15.7 ± 2.8 mmol/L vs. 6.7 ± 1.8 mmol/L to 20.0 ± 0.7 mmol/L), Bearhug (101.8 ± 3.5 kg to 120.8 ± 5.0 kg vs. 85.7 ± 2.9 kg to 117.1 ± 3.4 kg) and handgrip (45.1 ± 1.6 kg to 55.1 ± 2.6 kg vs. 35.3 ± 2.0kg to 47.7± 2.4 kg) tests. An improved understanding of the effects of competitive wrestling on physiological parameters is valuable for coaches and practitioners, developing the relationship between the prescribed contextual training and the expected neurophysiological responses. © 2020